Fan Shouyi, a bridge between China and the West under the rite controversy - Meynard, Thierry (Annales Missiologici Posnanienses, 2023)
Much has been written about Matteo Ricci and others Western missionaries in China, and less attention has been given to Chinese Catholics. We present here the fascinating story of Fan Shouyi, a Chinese Catholic who came to Europe and decided to become a Jesuit. Returning to China, he played a role in the relations between pope Clement XI and the emperor Kangxi, a role not easy but quite constructive.